Isomorphic Learning Model Based on the Qur'an in Early Childhood - Made Saihu (STAI Hubbulwathan Duri, 2021)
This study discusses the isomorphic learning model based on the Qur'an in early childhood Islamic education. This study uses a descriptive qualitative method which was confirmed by three educators at PIAUD Amanah Bunda Tangerang during December 2019 to February 2020 through deep interviews. Research shows that in applying the isomorphic learning model, educators have several obstacles, namely: lack of parental support, lack of support from the surrounding environment, and lack of ability of educators to explore educational concepts in the Qur'an. Some of these obstacles can be overcome by conducting home visits, educational partners, and upgrading the study of the Qur'an. This study also shows that to foster noble character, it is carried out by introducing moral education, worship education and monotheism education. If associated with the isomorphic learning model, moral education is related to the disciplines of psychology, sociology, anthropology. While worship education is closely related to the science of health, nutrition and physiology. Finally, monotheism education is related to the science of neuroscience, aiming to optimize the work of the mind to study all of Allah's creations that exist on earth and in the sky. Thus, the isomorphic learning model based on the Qur'an which focuses on aspects of faith and morality as the foundation for early childhood Islamic education becomes an obligation to be implemented.